PROJECT CLMM (Contextualized Learner Material in Mathematics) an Input on Pupils Academic Performance - Hizon, Isabelita (JPAIR Institutional Research, 2019)
Mathematics subjects are always regarded as one of the most difficult courses to teach and learn. The proponent, in collaboration with the Learning Resource Management Division, comes up with an idea of contextualizing the learning resource material in Mathematics. This descriptive-quantitative study focused on the implementation of Project CLMM and its input on pupils’ academic performance of Grade 6 pupils in Puting Lupa ES, Hornalan ES, Majada Out ES, Paciano ES, JRMS, and Calamba ES. Data collected were the results of the pretest and posttest and first grading grade in mathematics and the feedback of CLMM.The result showed that there was a significant difference existed between the pretest and posttest of the pupils’ respondents by 34.62%. Increased on the number of high performing pupils while decreased in the number of low performing pupils were evident. Some of the items on the CLMM need to modify like engage yourself. The results implied that CLMM was properly implemented and help improve the academic performance of pupils in mathematics.